Clearing the Course: Folio 348 of the Nepalese Gaṇḍavyūha-sūtra in the Cleveland Museum of Art - Mace, Sonia Rhie (Religions, 2020)
The final 15 folios of the Nepalese illuminated palm-leaf manuscript of the Sanskrit Gaṇḍavyūha-sūtra of c. 1100 have more paintings per page, larger picture planes, and different types of scenes than are found on the leaves surviving from the first 340 folios. One example is Folio 348 in the Cleveland Museum of Art, which has been painted with scenes of a bodhisattva tossing a blue-skinned heretic, an unusual image of a monk or upāsika wearing blue robes, and a Vajrācārya priest setting a Hindu rishi ablaze. From the point of view of the Mahāyāna Buddhist makers of this manuscript, these figures may personify the wrong views that derail pilgrims on the bodhisattva path to enlightenment. The dramatic shift in imagery appears to reflect the transition from the end of the inspirational pilgrimage of Sudhana to the popular, protective dhāraṇī verses of the Bhadracarī that form the finale to the text. The scenes of destruction and elimination of heretical figures correspond with sentiments in the Bhadracarī, indicating that the artists understood the structure and content of the text.